2021
DOI: 10.4103/sja.sja_352_21
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric and accuracy comparison of three commonly used questionnaires for the diagnosis of neuropathic pain

Abstract: Objectives: Diagnosis of neuropathic pain is challenging. Recently, scientists developed multiple questionnaires to expedite this diagnosis including the Self-completed Leeds Assessment of Neuropathic Symptoms and Signs (S-LANSS), Douleur Neuropathique 4 questionnaire (DN4), and Neuropathic Pain Questionnaire–Short Form (NPQ-SF). Materials and Methods: We conducted a prospective cohort study to compare the psychometric characteristics and accuracy of the three questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…In the current study, the DN4 demonstrated acceptable reliability via Kuder-Richardson Formula 20 (KR-20 = .723) and in a range similar to that found by others (Abolkhair et al, 2021).…”
Section: Np Symptomssupporting
confidence: 88%
See 2 more Smart Citations
“…In the current study, the DN4 demonstrated acceptable reliability via Kuder-Richardson Formula 20 (KR-20 = .723) and in a range similar to that found by others (Abolkhair et al, 2021).…”
Section: Np Symptomssupporting
confidence: 88%
“…Affirmative responses are summed for a total score (Bouhassira et al, 2005, 2008). The DN4 has demonstrated higher reliability relative to other general NP measures (Abolkhair et al, 2021) and is reliable and valid in the assessment of SCI-related pain (Hallström & Norrbrink, 2011). In the current study, the DN4 demonstrated acceptable reliability via Kuder–Richardson Formula 20 (KR-20 = .723) and in a range similar to that found by others (Abolkhair et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The value of AUC ranges from 0.5 to 1. The diagnostic value is acceptable when the score is between 0.71 and 0.8, excellent when it is 0.81–0.9, and outstanding when it is >0.9 ( 46 ). DeLong’s test ( 47 ) was performed to compare multiple ROC curves.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies also found that the S-LANSS showed higher specificity than did the DN4 24 , 28 or PDQ 28 in low back pain 28 and polyneuropathy. 24 Furthermore, S-LANSS previously showed similar discriminant validity for NP 55 and demonstrated superiority to other tools (eg, DN4, 55 PDQ 24 ). These findings could be explained by the items for self-assessment of allodynia and hyperalgesia included in the S-LANSS targeting the affected area and potentially enabling more accurate identification of the pathophysiology related to pain.…”
Section: Discussionmentioning
confidence: 80%